Transnational civil society and the consumer-friendly turn in financial regulation - Lisa Kastner (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2013)
The literature on financial regulation has typically emphasized the role of the powerful financial industry in shaping regulatory outcomes. However, capture theories cannot explain the prominence of financial consumer protection in post-crisis reform agendas. By contrast, this paper argues that, despite their collective action disadvantage, a polymorphous network of civil society organizations was able to gain momentum after the financial crisis and to influence the financial reform process. In this policy window, where decision-makers were looking out for an alternative source of expertise, a transnationally connected civil society network successfully raised the issue of consumer protection on reform agendas in tandem with public entrepreneurs and on the back of a popular backlash against big finance. This argument will be explored through a comparative study of the impact of transnational pressures on policy-makers in Europe and the US in the immediate aftermath of the crisis. In the conclusion, the paper discusses the substance of the financial reforms that have been undertaken.
Keywords: 330